Keputusan Keuangan Memoderasi Pengaruh Struktur Kepemilikan Institusional terhadap Praktik Penghindaran Pajak - Moeljono Moeljono (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of the company's institutional ownership structure on tax avoidance practices and the existence of financial decisions (investment decisions, funding decisions and dividend policies) as moderating variables for the interaction of the influence between the company's institutional ownership structure on tax avoidance practices. The subjects of this research were manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The sample selection used the purposive sampling method and obtained 30 companies that meet the criteria. The data used were secondary data from financial reports and annual reports, while the data analysis techniques used are descriptive statistical analysis and multiple regression analysis. The moderation test used MRA (Moderating Regression Analysis) using SPSS 26. The results showed that the company's institutional ownership did not affect tax avoidance practices. Furthermore, testing using the MRA shows that financial decisions as moderating variables (investment decisions, funding decisions and dividend policies) are not able to strengthen the effect of corporate institutional ownership on tax avoidance.